Modelling South Africa's economic transformation and growth: A prospective and retrospective analysis - Ramos E. Mabugu; Nyiko Worship Hlongwane (Economies, 2025)
The economic downturns in South Africa present a significant threat, with the potential to disrupt the nation's notable advances in addressing the persistent challenges of high unemployment, widespread poverty and stark inequality. In the absence of substantial and extensive structural transformation, South Africa's aspirations to achieve its ambitious development goals may remain unattainable. Building on the precedent of a blend of literature review, comprehensive ex post analysis, and applied general equilibrium modelling tailored for ex ante assessments, this paper assesses options and impacts of alternative ambitious developmental interventions. The results indicate that, despite implementing a variety of strategies, there remains a disheartening underperformance in economic indicators. However, ex ante evaluations indicate that with targeted interventions and supportive government policies, the country can achieve economic growth and job creation. Simulation results identify sectors of personal and social service activities, transport, finance, and insurance as having the most formidable potential to significantly reduce unemployment while simultaneously catalysing robust economic growth. These pivotal sectors, nestled within the broader services and industries, are uniquely poised to bolster overall productivity and diminish unemployment, while adeptly absorbing a considerable influx of highly educated and skilled labour. This suggests that South Africa can decisively accelerate its economic progress by embracing a dual-pronged approach: fostering structural shifts towards manufacturing and services, while steadfastly advancing the upskilling of its dynamic workforce.
Keywords: E01; C05; O40; O47; 330; economic transformation; stock tacking; economic growth; South Africa